Health and ethnic minorities in the Media: An analysis of the coverage of Indigenous peoples' health before and during the COVID-19 pandemic in Peru - Guadalupe Madge, Elena (2024)
This essay about the media coverage of Indigenous peoples' health in Peru reveals a consistent lack of depth and nuance. Pre-pandemic, domestic outlets echoed governmental perspectives without critical analysis of the indigenous healthcare conditions; while international media, though acknowledging discrimination and primarily focused on environmental issues, did not make explicit connections between both topics and the limited access to health services in these communities. This trend continued during the pandemic, with domestic coverage remaining superficial and international media largely ignoring the pandemic's impact on indigenous communities. It reveals a persistent racism within the press, so it is possible to affirm the historical power imbalances stemming from colonialism continue shaping news framing, agenda-setting and the determination of news value both domestically and internationally, being that media representations in a post-colonial context reinforce stereotypes of formerly colonized people, whose voices and issues are considered newsworthy only when they if fit certain narratives.